A Smart Building as a Cyber Pyhsical System - Hanife APAYDIN OZKAN (International Journal of Applied Methods in Electronics and Computers, 2016)
In recent years, systems consisting of both physical and computational elements, called Cyber Physical Systems (CPSs), have entered into our lives. These systems are becoming increasingly important because of their wide application area such as smart buildings, intelligent manufacturing processes, energy grids, healthcare devices, smart agriculture and etc. In this work, CPSs are considered by means of a smart building application. Firstly, CPSs are introduced and their features are explained. Then, a smart building is considered for emphasizing and illustrating the importance of CPSs. In order to display working mechanism of computational and physical components of the building and to provide easy trace of the evolution of overall system, some physical components (smart AC, lighting system and smart TV) are developed via Petri net, which is a mathematical and graphical tool for modelling and analysing discrete event systems.